Pemanfaatan Teknologi Informasi HEC-HMS Pada Potensi Penerapan Rainwater Harvesting Di Perumahan Bumi Kilu Permai Kota Manado: Use of Information Technology HEC-HMS on Potential for Implementing Rainwater Harvesting in Bumi Kilu Permai, Manado City - Tumurang, Olivia Maria (Universitas Sam Ratulangi, 2024)
Abstract - Flood disasters are a seasonal threat that always occurs, an increase in surface flow discharge which has the impact of flooding due to lost absorption capacity and drought in the dry season. Techniques or methods are needed to prevent this, such as the eco-drainage concept that can be applied, including Rainwater Harvesting (RWH). Community participation in maintenance is needed to maintain the success of the ecodrainage system. It is hoped that the people living in the Bumi Kilu Permai Housing Complex can set an example in environmental maintenance implemented in their respective homes in dealing with the possibility of flooding. This research evaluates the potential for implementing a rainwater harvesting system in managing environmentally sound drainage. The method used to calculate the capacity of rainwater harvesting facilities uses monthly storage simulations. Rain distribution uses the HEC-HMS application to determine flood discharge hydrographs, Log Pearson Type III frequency analysis method. Calculation of discharge in gutters and also calculation of rainwater harvesting. The application of rainwater harvesting in the Bumi Kilu Permai housing complex by applying HEC-HMS 4.2.1 software shows that the peak flow hydrograph is 390 mm/hour. The use of an open rectangular gutter of 15 cm x 15 cm is still safe for a return period of 2 to 100 years with discharge on the roof is 0.210 m3/s. The average rainfall calculated using HEC_HMS 4.2.1 software was 25,527.32 liters. The tower used for rainwater harvesting is 1000 liters in size. With the monthly amount of water that can be stored for 1 month, it is 186,000 liters, while the amount of water that can be stored in the tower is 180,440.73 liters. Implementing rainwater harvesting for 1 house can reduce 1000 liters of surface water runoff. If 300 can withstand 300,000 liters of surface water runoff or runoff. Of course, this can help minimize the probability of flooding in Paniki Satu Village, which is located in front of the Bumi Kilu Permai Housing Complex and is in the Paniki Watershed. Keywords: Rainwater Harvesting, HEC-HMS, Manado Abstrak - Bencana banjir adalah ancaman musiman yang selalu terjadi, peningkatan debit aliran permukaan yang membawa dampak terjadinya banjir akibat kapasitas resapan hilang dan kekeringan di musim kemarau. Diperlukan teknik atau metode untuk mencegah hal tersebut, seperti konsep ekodrainase yang dapat diterapkan diantaranya adalah Rainwater Harvesting (RWH). Peran serta masyarakat dalam hal pemeliharaan sangat dibutuhkan untuk tetap menjaga keberhasilan sistem ekodrainase.